Apoptosis-Associated Speck-Like Protein Containing a CARD Deletion Ameliorates Unilateral Ureteral Obstruction Induced Renal Fibrosis and Endoplasmic Reticulum Stress in Mice - Yao Xu; Yuqing Liu; Honglei Guo; Wei Ding (Mediators of Inflammation)
Inflammation might be one of the essential underlying mechanisms of renal fibrosis, which is considered a key pathological feature of end-stage renal disease and is closely associated with proteinuria and decreased renal function. Apoptosis-associated speck-like protein containing a CARD (ASC), identified as the central structure of inflammasome, is involved in the progression of interstitial fibrosis; however, its signal transduction pathways remain unclear. In the present study, we performed unilateral ureter obstruction (UUO) in both wild-type and ASC deletion mice to determine the contribution of ASC to renal fibrosis. Compared with control groups, UUO significantly induced renal fibrosis and collagen deposition, as evidenced by photomicrographs. ASC deletion attenuated renal injury, reduced cell infiltration and the release of inflammatory cytokines, protected against apoptosis, and downregulated the PRKR-like endoplasmic reticulum kinase (PERK) pathway of endoplasmic reticulum (ER) stress. Our data identify a novel role of ASC in the regulation of renal fibrosis and ER stress after UUO, strongly indicating that ASC could serve as an attractive target in the treatment of chronic kidney disease.